Non-volatile organic transistor memory based on black phosphorus quantum dots as charge trapping layer - Kumari, Priyanka (2020)
High performance organic nano-floating gate transistor memory (NFGTM) has important prerequisites of low processing temperature, solution–processable layers and charge trapping medium with high storage capacity. We demonstrate organic NFGTM using black phosphorus quantum dots (BPQDs) as a charge trapping medium by simple spin-coating and low processing temperature (< 120 °C). The BPQDs with diameter of 12.6 ± 1.5 nm and large quantum confined bandgap of ~2.9 eV possess good charge trapping ability. The organic memory device exhibits excellent memory performance with a large memory window of 61.3 V, write-read-erase-read cycling endurance of 10 3 for more than 180 cycles and reliable retention over 10,000 sec. In addition, we successfully improved the memory retention to ON/OFF current ratio > 10 4 over 10,000 sec by introducing PMMA as the tunneling layer.